Differential Diagnosis of Colonic Strictures: Pictorial Review with Illustrations from Computed Tomography Colonography. Issue 3 (August 2015) - Wan, Daniel; Bruni, Silvio G.; Dufton, John A.; O'Brien, Paul
Strictures of the colon can lead to significant morbidity requiring surgical management. The etiology of strictures is broad and generally categorized as benign, malignant, or pseudostrictures. Computed tomography (CT) is a crucial imaging modality in the assessment and characterization of colonic pathologies but colonoscopy remains the diagnostic gold standard. However, in the setting of incomplete colonoscopy due to strictures, the imaging features of CT will be relied on. This review will focus on the CT features of different colon pathologies leading to strictures and will be illustrated with images from 10 years of experience with CT colonography at our institutions from 2002-2012 (Hotel Dieu Hospital, Queen's University and Mount Sinai Hospital, University of Toronto).